Performances of Water Management, Foliage Dressing, and Variation Screening in Controlling the Accumulation of As and Cd and Maintaining the Concentrations of Essential Elements in the Grains of Rice Plant - Lei, Lei; Lv, Haiqin; Yu, Yang; Hu, Ronggui; Wang, Ruigang; Xu, Yingming; Ding, Yongzhen; Feng, Renwei; Fan, Zhilian (Frontiers in Environmental Science, 2018)
This study was conducted to understand why and how the technologies of variety screening, foliar dressing, and water management can reduce As/Cd accumulation and affect the concentrations of essential elements in different rice plants. In Trial I (variety screening), the grain As and Cd concentrations in Zhongguyou1361 variety (P3) were both lower than their individual National Food Hygiene Standard of China (NFHSC) under insufficient field drying condition. The P3 also had a relatively high yield and high essential element contents among 15 selected rice varieties. In Trial II (foliar dressing), selenite foliar spray showed a better ability than silicate to reduce the grain As content in Guangliangyou1128 variety (P1). However, spraying Se and Si onto the Fengliangyou1 variety (P2) both showed a limited effect on the grain As and Cd contents, suggesting a different effect of Se on grain As content in various rice varieties. The insufficient field drying in Trial II resulted in the grain Cd content being lower but the grain As content being higher than their individual NFHSC in both P1 and Fengliangyou1 (P2) varieties. Se or Si did not affect the yields and the grain contents of most essential elements in P1 and P2. In Trial III (water management), increasing field drying time enhanced the Cd content but reduced the As content in the grains of P1, P2 and P3, and maintained their yields. Similar to the results of Trial II, the changes in soil pH, organic matter concentration and elemental available concentrations could hardly be used to explain why the contents of corresponding essential elements kept approximately constant in the grains of different rice varieties. Foliar dressing with selenite combined with water regulation can simultaneously reduce the As and Cd contents, and maintain the yields and the essential element contents in the grains of rice plants cultivated in As- and Cd- contaminated soil.